Peranan Guru Bimbingan dan Konseling Melalui Pendidikan Karakter Dalam Mengatasi Bullying di SMP 4 Negeri Bukittinggi - A, Angreni; Putra, Dodi Pasila; R, Rahmawati (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Â Education is known as a bridge to obtain knowledge, with education it is hoped that it will be able to create quality individuals, both in terms of religion, personality, intellectual, based on Law no. 20 of 2003 concerning national education states that the aim of education is to create individuals with noble character. However, in education, many students still experience problems, especially bullying behavior. The aim of the research is to find out the extent of the role of teachers, especially guidance and counseling teachers, in dealing with these actions. The research method is phenomenology based on current events, this type of research uses a qualitative descriptive approach, data collection is based on observation, direct observation in the field, sources of teacher informants, students, etc. The research results illustrate that the role of guidance and counseling teachers through character education to overcome bullying behavior is running optimally, all school parties have collaborated with parents in handling cases by providing direction regarding the negative impacts of bullying. In this case, there is also a way for guidance counselors to minimize bullying behavior, namely by implementing classical guidance services using sociometric administration to find out what the state of children's social relations are in the classroom and implementing individual counseling services according to the needs of students.